Corporate Social Responsibility and Financial Performance in the Chinese Pharmaceutical Sector: The Roles of Technological Innovation and Media Coverage - Jin Wang; Singha Chaveesuk; Vasu Keerativutisest (My University, 2025)
The pharmaceutical industry has been developing rapidly in recent years, and concerns have been widely raised about social responsibility for the safety of people’s lives. This research aims to investigate the impact of CSR on CFP of listed pharmaceutical companies in China. This study was based on the data of pharmaceutical listed companies from 2010 to 2020 as a sample and built regression models for the effects of pharmaceutical corporate social responsibility (CSR) on corporate financial performance (CFP) based on the indirect effects of technological innovation and media coverage. The two-way fixed effect method, the systematic generalized method of moments estimation (SYS-GMM), and the Bootstrap method are adopted for the regression analysis of the model. The research found that (1) CSR positively affected CFP; (2) CSR positively affected technological innovation, while technological innovation partially mediated between CSR and CFP; and (3) both positive and negative media coverage negatively moderated the relationship between CSR and CFP as well as the relationship between CSR and technological innovation. In addition, both positive and negative media coverage negatively moderates the mediation path of “CSR–corporate innovation–CFP”.
Keywords: Corporate Social Responsibility Reporting